GLP-2: A POORLY UNDERSTOOD MEDIATOR ENROLLED IN VARIOUS BARIATRIC/METABOLIC SURGERY-RELATED PATHOPHYSIOLOGIC MECHANISMS - CAZZO, Everton (Arq Bras Cir Dig, 2016)
INTRODUCTION: Glucagon-like peptide-2 (GLP-2) is a gastrointestinal hormone whose effects are predominantly trophic on the intestinal mucosa. AIM: Critically evaluate the current literature on the influence of bariatric/metabolic surgery on the levels of GLP-2 and its potential clinical implications. METHOD: s: Narrative review through online research on the databases Medline and Lilacs. There were six prospective human studies, two cross-sectional human studies, and three experimental animal studies selected. RESULTS: There is evidence demonstrating significant increase in the levels of GLP-2 following gastric bypass, Scopinaro operation, and sleeve gastrectomy. There are no differences between gastric bypass and sleeve gastrectomy in regards to the increase in the GLP-2 levels. There is no correlation between the postoperative levels of GLP-2 and the occurrence of adequate or insufficient postoperative weight loss. CONCLUSION: GLP-2 plays significant roles on the regulation of nutrient absorption, permeability of gut mucosa, control of bone resorption, and regulation of satiety. The overall impact of these effects potentially exerts a significant adaptive or compensatory effect within the context of varied bariatric surgical techniques.